Delayed splenic rupture following cardiopulmonary exercise testing. Issue 1 (18th January 2016) - Davies, Iwan; Windsor, Alastair; Meecham, Lewis
Summary: Cardiopulmonary Exercise Testing (CPET) is widely considered to be a safe test [1] and the risk of death is estimated to be in the region of 1 per 20000 [2]. We report the case of a 75‐year‐old female presenting with life threatening splenic rupture following CPET.